Mudirul Ma’had Strategies In Internalizing Students’ Moral Values At Nurul Ilmi Riau In The Social Media Era - Sumardi; Muhammad Alfi Syahrin; Ahsan Hakim (Jurnal Pendidikan Indonesia, 2026)
This study analyzes the strategies of the mudirul ma’had and their effectiveness in internalizing students’ moral values in the era of social media as part of digital and hybrid learning challenges in Islamic boarding schools. The expansion of digital technology has transformed students’ learning patterns and moral behavior, requiring pesantren leaders to adopt adaptive and value-based educational strategies. This research employed a qualitative case study approach conducted at Nurul Ilmi Islamic Boarding School, Tualang, Siak Regency, Riau Province. Data were collected through observations, in-depth interviews, and documentation involving the mudirul ma’had, teachers (ustadz/ustadzah), students, and parents. Data analysis followed the stages of data reduction, data presentation, and conclusion drawing, supported by triangulation to ensure validity. The findings indicate that the mudirul ma’had implemented integrated strategies, including moral role modeling (uswah hasanah), habituation of religious practices, regulation and supervision of digital media use, enforcement of pesantren discipline, and the integration of religious digital literacy within daily learning activities. These strategies proved effective in strengthening students’ moral awareness, improving ethical behavior in social media interactions, and fostering responsibility in both online and offline learning environments. Nevertheless, the effectiveness of moral internalization is influenced by family background and students’ external social environments. This study offers a contextual digital-religious moral education model that supports character development within hybrid learning settings in Islamic boarding schools.